Empirical test of a model of agenda setting - Carreón Guillén, Javier; Hernández Valdés, Jorge; García Lirios, Cruz (Acta Universitaria, 2014)
Although phenomenon of the establishment of a socio-political agenda has been studied in different contexts, the contrast of empirical models from its psychological dimensions has been confined to the prediction of group differences. In this regard, the groups differ by age ranges in reference to issues that were disseminated in the press from governmental decisions. The objective of this research is to contrast a reflexive relations model in the agenda setting from eight psychological dimensions. A cross-sectional study was conducted using a nonrandom sample of 312 students was used to estimate the normal distribution, reliability, validity, covariance structure and model fit [χ2 = 13.12 (3 df) p < 0.05, GFI = 0.975, RMR = 0.003, RMSEA = 0.001]. The results show that the dimensions of attitudes mantain a dependency relationship with the agenda setting (β = 0.81). Results were discussed in reference to the studies reported in literature.
Keywords: Array; Array; Array; Array; Array